Intense exercise and endurance-training program influence serum kinetics of muscle and cardiac biomarkers in dogs - Cerqueira, Juliana Aparecida [UNESP]; Zamora Restan, Wilmer Alejandro [UNESP]; Fonseca, Mayara Goncalves [UNESP]; Catananti, Lucas Azevedo [UNESP]; Mendes de Almeida, Maria Luiza [UNESP]; Feringer Junior, Walter Heinz [UNESP]; Pereira, Gener Tadeu [UNESP]; Carciofi, Aulus Cavalieri [UNESP]; Ferraz, Guilherme de Camargo [UNESP] (Elsevier B.V., 2018)
Few data exist on the physiological consequences of an incremental exercise test (IET) and training in dogs. Here we evaluated the effect of an endurance-training program (ETP) on the kinetics of the serum biomarkers: creatine kinase (CK), aspartate aminotransferase (AST), myoglobin, cardiac troponin I (cTnI), and creatine kinase isoenzyme MB (CK-MB). Eighteen Beagle dogs were assigned to three groups: sedentary (S), untrained (U), and trained (T). The dogs from the groups T and U underwent IET, and their lactate threshold (LT) was determined. The LT and velocity corresponding to the LT (VLT) was determined by visual inspection. The VLT was utilized to determine the training intensity level. Thus, the dogs from group T underwent an eight-week aerobic conditioning program with the intensity training set to 70-80% of the VLT. Next, dogs from the groups T and U have submitted to IET again. The group S did not undergo IETs or training. The maximal velocity (Vmax) at which the dog achieves in the IET and heart rate were determined. For biomarkers, venous blood samples were collected before the experimental procedure (baseline) and before and 1, 6, 12, 24, 48, and 72 h after the IETs. VLT and Vmax increased in group T (P < .05), indicating an improvement in dogs' aerobic and anaerobic fitness. CK and AST rose (P < .05), peaking 6 h after both IETs and returning to baseline levels after 12-24 h. Levels of cTnI and myoglobin were unaltered. CK-MB peaked 1 h after the IETs and returned to baseline levels after 12 h (P < .05). We concluded that ETP improved the aerobic capacity of the dogs without any skeletal or cardiac muscle injury.
Keywords: creatine kinase; aspartate aminotransferase; myoglobin; cardiac troponin I; lactate; heart rate